Strategi Kolaborasi Orang Tua dan Guru dalam Penguatan Pendidikan Akhlak Remaja di Era Digital (Studi pada SMKN 1 Blora) : Penelitian - Zulfa Nur Kamila; Ahmad Saiful Rizal; Achmad Abdul Azis (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education plays a strategic role in shaping national character and preparing future generations to compete in the global era. Its function is not limited to the transfer of knowledge but also includes instilling moral values, building personality, and fostering social awareness. In the context of Islamic education, collaboration between parents and teachers becomes a fundamental foundation for nurturing adolescents’ character, especially in the digital era, which brings new challenges such as declining discipline, weak digital ethics, and low social awareness. This study aims to analyze strategies of collaboration between parents and teachers in strengthening adolescents’ moral education at SMKN 1 Blora, while also identifying obstacles encountered in the collaboration process, such as digital literacy gaps, parents’ time constraints, and fragmented responsibilities between home and school. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using the Miles, Huberman, and Saldaña model. The findings reveal that forms of collaboration are manifested through intensive communication, parenting programs, supervision of technology use, habituation of religious activities, and parents’ involvement in school activities.